Potensi Tumbuhan Obat Dalam Upaya Pemanfaatan Lahan Pekarangan Oleh Masyarakat Desa Cimenteng Kawasan Taman Nasional Ujung Kulon - Upik Nurmayulis; Nuniek Hermita (Faculty of Agriculture, Pattimura University, 2015)
The objective of research was to identify potential plants in order to be utilized as medicinal plant in the yard by community at Cimenteng village in Ujung Kulon National Park Area. Survey and interview method has been carried out with quantitative and qualitative approach. Data was collected by using explorative survey with interview and direct observation in fieldl; and analyzed descriptively. The result indicated that 48 plants have been identified and shown medicinal property; among them 20 plants cultivated in yard and 28 plants grown wildly around the yard. If the plants managed well, then Cimenteng village has an opportunity to be developed as agrotourism village. More than 30 medicinal plants area can be developed as tourism object which is economically will give a benefit for the community.